(3eYGdLI GNHGQ hbVGjG GSQGFjd ai GdbfhGJ GdaVGFjI GdGNHGQjI hGJLGgGJ GdfNHI fMhgG (B/ s - (3OYGA CMeO eMeO GdHfGs; (3GfTQGM GdTGd (B: s ((3GdbGgQI (B: s (3OYGA CMeO eMeO GdHfG (B: s, 2015)
(3GSJgOaJ gPg GdQSGdI GdJYQa Ydi cjajI eYGdLI GNHGQ hbVGjG GNHGQ hbVGjG GSQGFjd ai GdbfhGJ GdaVGFjI GdGNHGQjI GdYQHjI GdGLfHjI GdehLgI HGddZI GdYQHjI hGJLGgGJ GdfNHI fMh gPg GdeYGdLI GdGNHGQjI hJbjjegG hbjGS GJLGgGJge hSdhcge fMh ESQGFjd hGdESQGFdjjf (B{u(32018(B} (3HGdJWHjb Ydi fTQGJ GdMUGO GdGNHGQi ai NeS bfhGJ GNHGQjI JVefJ bfGI Gdfjd ddGNHGQ GdeUQjI h bfGI adSWjf Gdjhe(B: (3h bfGI ScGi fjhR YQHjI(B: (3h bfGI GdMQI GdCeQjcjI hbfGI GdENHGQjI GdjghOjI(B: (3h Pdc ef NdGd ELQGA OQGSI JMdjdjI ddeMJhi h GdNWGH GdebOe HGdfTQGJ ai gPg GdbfhGJ(B: (3HGSJNOGe fehPLq Ca(B.(3Oi(B.(3Bqi h gh fehPL jLeY Hjf fXQjI GdCWQ h COhGJ eONd JMdjd GdNWGH h GdUhQI GdEYdGejI(B: (3Edi LGfH ELQGA OQGSI ejOGfjI Ydi YjfI ef GdfNHI GdGcGOjejI h GdEYdGejI h GdSjGSjI GdeUQjI dOQGSI GJLGgGJge fMh eYGdLI CNHGQ h bVGjG ESQGFjd HfTQGJ GdCNHGQ ai GdbfhGJ GdENHGQjI GdNeSI ehVY GdOQGSI(B: (3h JMOjO GJLGgJge h Sdhcge fMh ESQGFjd h GdESQGFjdjjfs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdGYdGe (B- (3bSe GdGPGYI hGdJdjaRjRfs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdGNHGQ s; (3GdeYGdLI GdGNHGQjIs; (3fTQGJ GdGNHGQs